COVID-19 in patients with rheumatic diseases in northern Italy: a single-centre observational and case–control study. (September 2020) - Fredi, Micaela; Cavazzana, Ilaria; Moschetti, Liala; Andreoli, Laura; Franceschini, Franco; ,; Airò, Paolo; Bazzani, Chiara; Crisafulli, Francesca; Filippini, Matteo; Frassi, Micol; Gerardi, Maria Chiara; et al.
Summary: Background: The highest number of COVID-19 cases in Italy have been reported in Lombardy, a region in northern Italy. We aimed to analyse the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients with rheumatic and musculoskeletal diseases living in a district of Lombardy with a high prevalence of COVID-19. Methods: We did a single-centre observational study at the Azienda Socio Sanitaria Territoriale (ASST) Spedali Civili of Brescia, Italy. We collected data from patients with rheumatic and musculoskeletal diseases enrolled in our outpatient clinic to identify confirmed or possible cases of SARS-CoV-2 infection. Data were collected through a survey that was administered via telephone or in the outpatient clinic by rheumatologists. We also did a case–control study of all patients with confirmed COVID-19 pneumonia and rheumatic and musculoskeletal diseases who were admitted to the ASST Spedali Civili of Brescia during the study period. Cases were matched by age, sex, and month of hospital admission to at least two controls admitted to the same hospital for COVID-19 pneumonia during the study period. Findings: Between Feb 24 and May 1, 2020, we collected data from 1525 patients with rheumatic and musculoskeletal diseases: 117 (8%) presented with symptoms that were compatible with COVID-19. 65 patients had a swab confirmation of SARS-CoV-2 infection, whereas 52 presented with a spectrum of symptoms indicative of COVID-19 but were not swab tested. Patients with confirmed COVID-19 were older than those with suspected COVID-19 (median age 68 [IQR 55–76] years vs 57 [49–67] years; p=0·0010) and more likely to have arterial hypertension (33 [51%] vs 14 [27%] patients; odds ratio [OR] 2·8 [95% CI 1·3–6·1]; p=0·031) and obesity (11 [17%] vs 1 [2%]; OR 11·0 [1·3–83·4]; p=0·0059). We found no differences in rheumatological disease or background therapy between confirmed and suspected COVID-19 cases. 47 (72%) of the 65 patients with confirmed COVID-19 developed pneumonia that required admission to hospital. 12 (10%) deaths occurred among the 117 patients with confirmed or suspected COVID-19 (ten in those with confirmed COVID-19 and two in those with suspected COVID-19). Deceased patients with confirmed COVID-19 were older than survivors (median age 78·8 years [IQR 75·3–81·3] vs 65·5 years [53·3–74·0]; p=0·0002). We observed no differences in sex, comorbidities, or therapies between the deceased patients and survivors. The case–control study comprised 26 patients with rheumatic and musculoskeletal diseases and COVID-19 pneumonia and 62 matched controls. We found no significant differences between cases and controls in duration of COVID-19 symptoms before admission, duration of stay in hospital, or the local chest X-ray scoring system. Glucocorticoids were used for severe respiratory manifestations related to lung involvement in 17 (65%) of 26 cases and tocilizumab in six (23%) of 26; thrombotic events occurred in four (15%) of 26 cases. Four (15%) of 26 cases and six (10%) of 62 controls died during the study period. Interpretation: In this cohort of patients with rheumatic and musculoskeletal diseases in a geographical region with a high prevalence of COVID-19, a poor outcome from COVID-19 seems to be associated with older age and the presence of comorbidities rather than the type of rheumatic disease or the degree of pharmacological immunosuppression. Funding: None.